Micro-shear Bond Strength of a Nanofiller Bonding agent with and without Thermocycling in a Newly Invented Device - Zahra Jaberi Ansari; Hamid Khalili; Mohammad ali Keshavarz; Manoosha Amiri Siavashani (Islamic Dental Association of Iran, 2013)
Background and Aim : Estimation of the survival of dental materials is especially important when manufacturing new materials. Thermocycling can greatly help in this respect. The purpose of this study was to evaluate micro-shear bond strength of a nanofiller bonding with and without thermocycling in a newly invented device .   Materials and Methods : In this experimental study, human third molars were sectioned into 1.5 mm slices after extraction and disinfection. Clearfil Tri-S nanofiller bond was applied to the dentin part of sections according to the manufacturer's instructions. Clearfil AP-X composite resin was placed over the dentin using tubes with 0.75 mm internal diameter and one mm height and light cured. Specimens were randomly divided into three groups and subjected to thermocycling in a newly invented device for zero, 3000 and 5000 cyclesbetween 5±2°C and 55±2°C. Micro-shear bond strength was measured by microtensile tester with a cross-head speed of 0.5 mm/min. Obtained data were analyzed using one-way ANOVA. Tukey's test was used for multiple comparisons with a 95% confidence interval .   Results : The mean micro-shear bond strength after zero, 3000 and 5000 thermal cycles was found to be 19.27±4.56, 17.00±6.52 and 11.58±4.64 MPa, respectively. The reduction in bond strength between zero and 3000 thermal cycles was not statistically significant (P=0.3) but this reduction between zero and 5000, as well as 3000 and 5000 cycles was statistically significant (P<0.002 and P<0.03, respectively).   Conclusion: Increase in number of thermal cycles for more than 3000 reduces the micro-shear bond strength of Tri-S bonding agent .